Characteristics of Pregnant Women with Emesis Gravidarum in Midwife Self Practices 2020-2021 - Ni Komang Ayu Yuliari; Putu Sukma Megaputri (Jurma : Jurnal Program Mahasiswa Kreatif, 2023)
Emesis gravidarum is a discomfort or complaint that is most often felt by mothers, especially in the 1st trimester. This is due, in part, to the hormonal and psychological surge in the mother. The purpose of this study was to identify the characteristics of pregnant women who experience emesis gravidraum. This research method is quantitative with a cross sectional approach. The sampling technique in this study was total sampling with a total sample of 292 taken from 2019-2022 secondarily through the medical records of pregnant women. The results of the study reported that 45.5% of pregnant women felt emesis during early pregnancy. when viewed from the education of high school mothers as much as 46.1% experienced emesis. Mothers who are multigravida as much as 48.8% experience emesis. Furthermore, housewives who experienced emesis were 43.9%. The conclusion is that pregnant women with emesis gravidarum are often felt by mothers with the last high school education, multigravidas and housewives.